2020
DOI: 10.1002/ente.201901265
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric Harvesting by a Dual‐Tip Peak Power Multiplier under Airtight Condition

Abstract: Triboelectric nanogenerators (TENGs) are effective for harvesting mechanical energy and converting into electricity. Such devices have high output voltage and low current, appearing as high output impedance. Impedance mismatches involving these devices create challenges in power usage, storage, and management. Herein, a dual‐tip‐assisted TENG is developed and its electrical output performance under airtight condition is investigated. The generated charges can rapidly accumulate at the dual tip and produce a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Researchers have found that the sharpness and number of discharge electrodes, the pulse width of output voltage, the operating frequency of TENG, and the air environment are the factors influencing TENG with air breakdown. [77][78][79] Application of air breakdown in TENG not only enhanced the TENG output but also have developed many ingenious applications. Although in these applications, triboelectric charge decay is not reduced, some unexpected features of TENG are brought out.…”
Section: Application Of Air Breakdownmentioning
confidence: 99%
“…Researchers have found that the sharpness and number of discharge electrodes, the pulse width of output voltage, the operating frequency of TENG, and the air environment are the factors influencing TENG with air breakdown. [77][78][79] Application of air breakdown in TENG not only enhanced the TENG output but also have developed many ingenious applications. Although in these applications, triboelectric charge decay is not reduced, some unexpected features of TENG are brought out.…”
Section: Application Of Air Breakdownmentioning
confidence: 99%
“…So covering the substrate surface with the nanotube, nanoparticle, nanowire, and porous media can improve the performance of TENG due to an increased internal surface area as also suggested in 13 , 15 , 32 35 . On the other hand, TENG charge vanishes in humid environments because of the formation of water film on the surface 19 , 36 , 37 . Since humidity is ubiquitous in environments where TENG is used, improving the TENG operation in humid environments is of great importance as also indicated in 38 , 39 .…”
Section: Introductionmentioning
confidence: 99%